ASSESSMENT OF THE COMPETITIVENESS OF A PHARMACY IN THE PHARMACEUTICAL MARKET OF UKRAINE - YEVTUSHENKO, Victoria; LIASHEVSKA, Viktoriia; LYSENKO, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the concept of "enterprise competitiveness" and its importance in the modern system of enterprise functioning. Since competition is the main factor in the success and efficiency of any enterprise in the current economic situation, it is clear that without it, the full development of the economy in general is impossible. The success of any enterprise depends on the ability to compete in a certain product or service market. The relevance of this topic is due to the fact that due to the instability of the economic environment of the Ukrainian market, in particular the pressure to actively increase competition on the market in this sector, the issue of managing the competitiveness of business entities that provide pharmacy services is relevant and requires taking into account the specifics of the industry in order to find ways improve. The article examines the factors affecting the competitiveness of a pharmaceutical enterprise, analyzes a specific pharmacy in the city of Kharkiv and finds out its strengths and weaknesses, as well as the opportunities and threats of its activities, and suggests ways to improve the enterprise's competitiveness. Research on consolidation trends inherent in the retail pharmaceutical market in Ukraine. It has been established that the number of pharmacy chains is constantly growing, while the share of small pharmacy chains is gradually decreasing, and the share of mega chains is actively growing. The competitive advantages of the pharmacy network were studied and a SWOT analysis of the activity was carried out. In the course of this analysis, the evaluation of the criteria and the calculation of the values of the coefficients were carried out. In this way, it was found that the competitiveness of this pharmacy is high and the strengths completely eliminate the threats.
Keywords: competition; enterprise competitiveness; pharmacy; pharmaceutical market